Exploring a Good Language Learner’s Motivation - Khairunnisa Dwinalida (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2021)
Regarding the success in EFL learning, most of learners in the Indonesian context are still considered as unsuccessful and tend to be low motived. In related to this problem this study is aimed at finding out how motivation in EFL learning come out from a good learner and at reveal the aspects that can drive motivation from a good learner. A case study on an individual student was used in this study. The participant was purposefully and theoretically selected because she was considered as the best learner in the site. Student’s interview and classroom observation were used as the data collecting techniques. Iterative data collection and analysis using the concept of grounded theory were conducted continuously till theoretical pattern of concepts and categories were achieved. The findings of this research stated that the external factors were found more than the internal factors. It is concluded, then, external factors are dominating the source of the participant’s motivation. These findings suggest that teachers are expected to take the factors influencing motivation as stated in the findings as the consideration in improving students’ motivation in EFL learning. Keywords: motivation, good language learners